Advanced glycation end products: An emerging biomarker for adverse outcome in patients with peripheral artery disease. (November 2016) - de Vos, Lisanne C.; Lefrandt, Joop D.; Dullaart, Robin P.F.; Zeebregts, Clark J.; Smit, Andries J.
Abstract: Patients with peripheral artery disease (PAD) suffer from widespread atherosclerosis. Partly due to the growing awareness of cardiovascular disease, the incidence of PAD has increased considerably during the past decade. It is anticipated that algorithms to identify high risk patients for cardiovascular events require being updated, making use of novel biomarkers. Advanced glycation end products (AGEs) are moieties formed non-enzymatically on long-lived proteins under influence of glycemic and oxidative stress reactions. We elaborate about the formation and effects of AGEs, and the methods to measure AGEs. Several studies have been performed with AGEs in PAD. In this review, we evaluate the emerging evidence of AGEs as a clinical biomarker for patients with PAD. Highlights: An emerging biomarker is advanced glycation end products (AGEs). AGEs are strongly associated with peripheral artery disease (PAD). Skin autofluorescence (SAF) is a noninvasive method to assess skin AGEs. SAF identifies PAD patients at highest risk for local and cardiovascular end points.